Pengaruh Kepemimpinan Transformasional dan Lingkungan Kerja Terhadap Kinerja KSK Dengan Kepuasan Kerja Sebagai Variabel Intervening Pada BPS Provinsi Banten - Ritaudin, Didin; Mukhsin, Mohammad (Jurnal Riset Bisnis dan Manajemen Tirtayasa, 2018)
The purpose of this research was to determine the influence of transformational leadership, work environment and job satisfaction on the performance of employees and the influence transformational leadership and working environment throught job satisfaction. This research was conducted at BPS-Statistics of Banten Province, where the research method used is cause-effect method, the number of respondents amounted to 95 people who coordinator statistic of the sub-district (KSK) at BPS-Statistics of Banten Province. The data analysis technique used is descriptive analysis techniques and inferential analysis techniques to determine the degree of closeness of the relationship between the study variables. In the operationalization used SmartPLS 3.2.7. The results showed that the value of R-Square shows the value of 0.560% or 56.0%. it means that 56.0% performance is explained by transformational leadership variable an work enivornment, while the rest equal to 44.% explained by other factor 47.0% of job satistifaction variables are influenced by transformational leadership and employment performance while 53.0% others are influenced by other factor. The result of mediation test of job satisfaction can mediate on transformational leaderhip on performance, it is obtained whit T-statistics value 0.02 lower 0.05 at alpha 5%. While job satisfaction can’t mediate on work enivorment variables on performance as evidenced by the value of T-statistics of 0.98 which means lower than T-table 1.96 and the value of P values 0.33 greater than 0.05 at alpha 5%.The conclusion of this study is proven there is positively relationship between transformational leadership, work environment and job satisfaction on performance KSK, job satisfaction mediate trnasfomational leadership on performance while  job satisfaction doesn’t mediate the enivornment to performance.